Ibadah dan Perilaku Luhur (Kajian Psikologis dan Sosiologis) - Anisatul Luthfia; Syamsurizal Yazid (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research discusses the relationship between worship and noble behavior from both psychological and sociological perspectives, with the aim of identifying how worship, as a form of spriritual devotion, can influence individuals attitudes and behavior in the context of their social life. From a psychological view point, worship is understood as one of the means to achieve psychological well-being, inner peace, and self-control. Regular worship practices, such as prayer, fasting, and dhikr, are expected to enhance positive emotional quality and reduce stress and anxiety. On the other, from a sociological perspective, worship has an important social dimension, as it shapes norms and values in society and strengthens relationships among individuals within the community. Using a theoretical approach and empirical study results, this article concludes that worship performed with full awareness and understanding can be a source of strength for developing noble behavior both psychologically and socially.